Smart-Valleys approach for enhancing rice yield and reducing yield gap in West Africa - CGIAR Research Program on Rice (2021)
In the pilot countries, the Smart-Valleys approach has been adopted by non-development farmers organizations that are further scaling it without the direct involvement of AfricaRice.